Gender difference in the coronary risk factors amongst the patients with Acute Coronary Events (ACE) in Nepal - Rawat, B; Vaidya, Abhinav; Gurung, Jesson; Acharya, Subhash; Pandey, M; Verma, Pragya; Poudel, Pooja; Sodhi, H.S.; Karki, D.B.; Jha, SC (Nepalese Heart Journal, 2004)
The onset of symptomatic CAD is typically about 10 years earlier in men, but CAD incidence in women increases rapidly at menopause. Women have the same modifiable risk factors as that of men. Although Diabetes appears to cloner greater risk factors as that of men as may low HDL, cholesterol and plasma triglyceride. Not much data is available to asses If coronary risk factors are different in male Vs female population in South Asia.